Peranan amerika serikat di bank dunia:implentasi tanggung jawab sosialnya sebagai pemimpin dunia The Role ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT This study aims to reveal the role of the US in the World Bank that represents the country's social responsibility as the world leader. Things to discover are the position of the US in the establishment of the World Bank in Bretton Woods Conference, whereas at the same time and place the US was appointed to be the World Leader. The World Bank provides investment, advisory, and assistance to its member countries' development (especially developing countries) to reduce poverty so that their population have better living standard to come to the mainstream of globalization